Knowledge, attitude and behaviour of University of Ibadan women towards cancer of the cervix and its prevention (2012)
Objectives: The two commonest cancers in Nigerian women arc cancers of the breast and the cervix. Cancer of the cervix is the second commonest cancer and is a killer disease worldwide. The main objective of this study is to find out the knowledge, attitude and practices of the female university staff towards cancer of the cervix as a leadership group in the local effort towards cancer prevention. Methodology: A sample of 302 female staff of the University of Ibadan, which comprised 151 academic and 151 non-academic staff was studied. These were all the female members of staff who were met during the study visitation of all the departments on the main campus of the university and who were willing to participate in the study. A self-constructed and validated instrument called the knowledge, attitude and practice towards cervical cancer scale was used in collecting data for the study. Results: Two hundred and forty-two (79.1%) were aware of the disease, whereas 19.9% (60) were not aware. The academic staff were statistically significantly more knowledgeable of cervical cancer than the non-academic staff (p = 0.05). Two hundred and thirty-two (232 or 76.82%) have a positive attitude towards preventive measures for cancer of the cervix such as Pap smear or ascetic acid test. However, as much as 210 (73.5%) of the women had never undertaken a Pap smear or other screening test for the condition. Conclusion: There is need for more education and promotion of cancer screening and services in this locality.